2021
DOI: 10.1016/j.wdp.2021.100291
|View full text |Cite
|
Sign up to set email alerts
|

Moving toward rice self-sufficiency in sub-Saharan Africa by 2030: Lessons learned from 10 years of the Coalition for African Rice Development

Abstract: Highlights Contribution of the CARD policy to rice production in sub-Saharan Africa. Forecasts local rice supply and demand by 2030. Significant impact of the CARD policy was found on local production. Yield growth rate was not sustainable in most countries throughout the CARD period. Demand-pull factors development should be prioritized over the supply-shift actions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 31 publications
1
60
0
1
Order By: Relevance
“…In this context, we report some key results in which both climate and LULC current and future scenarios heavily influence rice and pulla group co-occurrence. Indeed, our current predictions show that the climatic suitability in the current scenario for rice crops is mainly found in two districts, Western and Eastern Africa, being in accordance with Arouna et al (2021) . The former shows high suitability for the pulla group, while the latter is suitable to this pest only in its northern part, posing at-risk rice crops in both cases.…”
Section: Discussionsupporting
confidence: 61%
“…In this context, we report some key results in which both climate and LULC current and future scenarios heavily influence rice and pulla group co-occurrence. Indeed, our current predictions show that the climatic suitability in the current scenario for rice crops is mainly found in two districts, Western and Eastern Africa, being in accordance with Arouna et al (2021) . The former shows high suitability for the pulla group, while the latter is suitable to this pest only in its northern part, posing at-risk rice crops in both cases.…”
Section: Discussionsupporting
confidence: 61%
“…Consequently, 71 % increase in paddy rice production during 2007–2012 was attributed to yield increases, and 29 % was attributed to harvested-area expansion ( Saito et al, 2015 ). However, between 2012 and 2018, the increase in yield was only 1.19 % annually, compared to an annual increase of 1.47 % between 2007 and 2012 ( Arouna et al, 2021a ). Despite the various policies implemented to boost local production, especially after the 2007/2008 global food crisis, local production in SSA has not been sufficient to meet the increasing demands of the population.…”
Section: Introductionmentioning
confidence: 99%
“…This contribution resulted from increases in area and yield of 23 per cent and 19 per cent, respectively. However, the study concluded that yield growth rate was not sustainable in almost two-thirds of the CARD countries because 'supply-push' factors, such as the promotion of new rice varieties, fertilisers and irrigation, were seen to have limited long-term effects on rice production (Arouna et al, 2021). Sustainable investments in 'demand-pull' factors involving value chain upgrading, such as improvements in the privately led modern milling sector, were less prominent in the NRDS.…”
Section: Key Challengesmentioning
confidence: 99%